2016
DOI: 10.1021/acs.joc.6b01446
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,3-Substituted Cyclobutanes by Allenoate-Alkene [2 + 2] Cycloaddition

Abstract: A method for the [2 + 2] cycloaddition of terminal alkenes with allenoates is presented. This process allows for the rapid synthesis of 1,3-substituted cyclobutanes in high yield under simple and robust reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…Delighted by the fact that the chloro-substituted substrates offer advantages in the initial hydroaminoalkylation reaction as well as in the subsequent Buchwald-Hartwig coupling, we used ortho-chlorostyrene (7) as the starting material for all further studies. To further investigate the scope of the hydroaminoalkylation of ortho-chlorostyrene (7) we performed corresponding reactions on a 2 mmol-scale with various functionalized secondary anilines (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) in the presence of 10 mol-% of catalyst II (Table 3). During this study, it was first found that para-methoxy-N-methylaniline (12) and para-thiomethyl-N-methylaniline (14) deliver the corresponding products 25b and 27b in good yields of 61 % and 58 %, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delighted by the fact that the chloro-substituted substrates offer advantages in the initial hydroaminoalkylation reaction as well as in the subsequent Buchwald-Hartwig coupling, we used ortho-chlorostyrene (7) as the starting material for all further studies. To further investigate the scope of the hydroaminoalkylation of ortho-chlorostyrene (7) we performed corresponding reactions on a 2 mmol-scale with various functionalized secondary anilines (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) in the presence of 10 mol-% of catalyst II (Table 3). During this study, it was first found that para-methoxy-N-methylaniline (12) and para-thiomethyl-N-methylaniline (14) deliver the corresponding products 25b and 27b in good yields of 61 % and 58 %, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The crude product was purified by flash chromatography (SiO 2 ). [15] A dried Schlenk flask was charged with methyltriphenylphosphonium bromide (42.87 g, 120.0 mmol), evacuated and backfilled with argon three times. Then the solid was suspended in Et 2 O (300 mL) and while vigorously stirring KOtBu (13.47 g, 120.0 mmol) was added.…”
Section: Wittig Reaction For the Synthesis Of Styrenes General Procementioning
confidence: 99%
“…Another example of thermal [2+2] cycloaddition included the Lewis acid catalyzed reaction of allene 72 with pina-col ester 73 giving cyclobutyl boronate 74 in 80% yield (Scheme 34). 76 Recently, photochemical [2+2] cycloaddition of maleimides and maleic anhydride 76 with alkenyl boropinacolates 75 was described by our group (Scheme 35). 77 In this case, the reaction was performed at a 1:1 ratio of the reagents using a 366 nm lamp irradiation and gave target products 77 in 49-93% yield.…”
Section: Scheme 32 [2+2] Cycloaddition Of Diphenylketene With Alkenylmentioning
confidence: 99%
“…The synthesis of the diastereoisomers of spiro LC candidates 11a and 11b also started from ketone 15 as illustrated in phosphine which was generated in situ from methyltriphenylphosphonium bromide (PPh 3 CH 3 Br), generated exo-methylene cyclohexane 18 in a very straightforward manner, and the product could be isolated by chromatography in 72% yield [17]. This olefin was then subject to a difluorocarbene cyclopropanation using TMSCF 3 and NaI, and this generated both isomers, 11a and 11b, in a ratio of 5:1, respectively.…”
Section: Synthesis Of Liquid Crystal Candidates 8-11mentioning
confidence: 99%
“…Synthesis of compounds 11. Reagents and conditions: a) PPh 3 CH 3 Br, t-BuOK, diethyl ether, 0 °C to rt, 72%[17]; b) TMSCF 3 , NaI, THF, reflux; c) recrystallization, 27%.…”
mentioning
confidence: 99%